Students’ Perspectives of HelloTalk Application: A Case Study - Taufan, Gullit Tornado; Wicaksono , Julien Arief (P3M Politeknik Negeri Jember, 2022)
This study enlivens the discussions under the topic of MALL. Specifically, this focused on a mobile-based application called HelloTalk; a language learning application that promises language learning and acquisition by communicating to native speakers and other language learning enthusiasts. This study aimed to investigate students’ perspectives on the use of HelloTalk, a mobile learning application that had not been widely used at the time being. In this case study, there were 41 English study program students, who were stuying in the third year of college, participating. The students were introduced to and given the opportunity to use the application in natural settings before responding the questionnaire from which the data were collected. The questionnaire was distributed to the participants to answer two main problems: 1) their knowledge of HelloTalk prior to the study and 2) their attitude towards the application. The data shows that most of the students, covering around two third of the total participants, did not know the, neither used, the application. Regarding students’ attitude towards HelloTalk, the data collected from the questionnaire indicates that 36 out of 41 showed positive and very positive attitude towards the application.